Examining the Relationship between ESG Disclosure, Financial Performance, and Company Value - Susilowati , Pusvita Indria Mei; Nordiansyah, Muhammad; Amiruddin, Amiruddin; Darmawati, Darmawati (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine the relationship between ESG disclosure, financial ratios (profitability, leverage, and Total Asset Turnover/TATO), and firm value as proxied by market capitalization. A quantitative approach was employed using secondary data from 18 industrial sector companies listed on the Indonesia Stock Exchange during the 2021–2023 period, resulting in 54 observations. The analysis methods included multiple linear regression, mediation tests based on the Baron & Kenny approach and Sobel test, as well as classical assumption testing. The results indicate that ESG disclosure is not significantly influenced by TATO, profitability, or leverage. However, profitability and ESG disclosure both show a positive and significant effect on firm value. In contrast, TATO and leverage have no significant impact. Moreover, there is no evidence that ESG disclosure mediates the relationship between financial variables and firm value. These findings highlight the importance of ESG disclosure as an independent factor that directly contributes to market value, regardless of traditional financial performance. Therefore, companies are encouraged to proactively enhance the quality of their ESG reporting to build investor trust and strengthen competitive positioning in the market.